Quantitative trait loci affecting pre-weaning weights in Baluchi sheep - SAGHI, D A; ASLAMINEJAD, A; TAHMOORESPUR, M; JANNS, L; NASSIRI, M; DASHAB, G R (The Indian Journal of Animal Sciences, 2013)
The objective of this study was to identify QTL affecting birth weight, 30, 60, 90 days weight in Baluchi sheep using data from half sib families and microsattelite in ovine chromosome (OAR1).The population study consisted of 434 Baluchi fat-tailed Iranian lambs from 11 half sib families, with progeny per family ranging from 29–54 individuals. Records on day of birth, sex, type of birth, age of dam and weight measurements at birth and 1 month intervals after birth up to weaning (90 days), were collected. Animals genotyped based on the panel of 8 microsattelite markers were selected based on positional candidate gene in OAR1. Lambs were genotyped for informative microsattelite markers markers that were heterozygous in their sire, on chromosome 1. Live weights measured at birth and 1 month interval to weaning (Bw, 30W, 60W, 90W) were treated as separate traits. Fixed effects for all live weights were year, sex, type of birth, age of dam. The day of birth or age at time of measurement was fitted as covariate for each trait. QTL analyses were conducted using a univariate multi-marker for half sib families, for each trait by interval mapping approach. Genome wide permutation indicated significant QTL for birth weight at closest to marker BMS2572 at 204.8 cM, for 30 and 60 days weights at the 213 and 189 cM, respectively, between the markers BMS2321 and BM7145 and for 90 days weight at 186.8 cM between the markers BMS2321 and BMS2572. The proportions of phenotypic variance explained by QTL were 18, 12, 15 and 21% for birth, 30, 60 and 90 days weight at its maximum. The absolute size of distinct QTL effects varied according to the trait means and QTL effects increased with age. Because of this reason traits were highly correlated so detection of QTL live weight as single trait fails to capture correlations between components.